Managing Food Quality Risk in Global Supply Chain: A Risk Management Framework - Arevalo Chavez, Pablo Jose (2009)
Today unsafe food products can have terrible results in the consumer and the supplier network. The purpose of the paper is to present an integrated conceptual framework for identify and assess effective the quality risk of a product along the global supply chain. The product quality risk concept has not totally researched. The proposed framework is divided in four main sections (i) Desired quality; (ii) Product quality; (iii) Organisational risk and (iv) Supplier management. A Central America medium distributer centre enterprise has been chosen to illustrate in a case study a firm’s quality risk problems in managing food. The proposed Product quality risk (PQR) framework is applied in the firm with the purpose of provides the elements to develop a programme to reduce quality risk. Through this paper the framework was developed mainly based on conceptual quality approach of Bozarth and Handfield (2005), Matoo et al. (2008) management supplier risk framework, Christopher et al. (2002) organisational risks and Roth et al. (2007) product quality risk factors. The current firm’s supply chain situation was explored, main problems were identified and possible solutions were suggested. The paper contributes in operations management basically in product quality risk in the specific field of multi-tier management network. The proposed framework is fully proactive management process that supports firm’s quality risk programs and improves the relationship with suppliers.